'Riots engulfed the city': An experimental study investigating the legitimating effects of fire metaphors in discourses of disorder. (May 2018) - Hart, Christopher
In Cognitive Linguistic Critical Discourse Studies (CL-CDS), metaphor is identified as a key index of ideology and an important device in the legitimation of social action. From this perspective metaphor is a cognitive-semiotic operation, invoked by metaphorical expressions in discourse, in which a source frame is mobilised to provide a template for sense-making inside a target frame, leading to particular framing effects. However, the extent to which metaphors in discourse genuinely activate an alternative frame and thereby achieve framing effects has recently been subject to question. Amid calls for more empirical forms of analysis in CDS, the article reports two experiments testing the legitimating framing effects of fire metaphors in discourses of disorder. Results show that images of fire and fire metaphors in the absence of competing images facilitate support for police use of water cannon in response to social unrest. The study not only justifies attention to metaphor in CL-CDS, but similar effects observed across semiotic modalities are interpreted as evidence in support of simulation-based theories of metaphor.